European civil society and human rights advocacy - Thiel, Markus 1973- (Pennsylvania studies in human rights, 2017)
Adherence to basic human rights norms has become an expected feature of states throughout the world. In Europe, the promotion and protection of human rights through national governments has been enhanced by the diversity of intergovernmental organizations committed to this cause. The latest addition to the continent's rights organizations arrived ten years ago when, based on the EU's Lisbon Treaty, the Fundamental Rights Agency (FRA) was created as a functional institution to highlight and improve human rights within EU member states. In contrast to other regulatory agencies in the EU, the FRA provides a research-based advisory function for EU institutions and legislation and performs a public-diplomacy function in promoting fundamental rights across EU member states.The linking of civil society with internal rights policies has yet produced very little scholarship.